Factors influencing risk of predation by subsidized predators on juvenile Mojave desert tortoises (Gopherus agassizii) - Collin J. Richter; Brian D. Todd; Kurt A. Buhlmann; Gabriella R. Barnas; Michel T. Kohl; Tracey D. Tuberville (Global Ecology and Conservation, 2024)
A persistent lack of juvenile recruitment in populations of the imperiled Mojave desert tortoise (Gopherus agassizii) has been attributed to artificially inflated populations of coyotes (Canis latrans) and common ravens (Corvus corax) in some areas. Subsidized by resources in the form of road-killed prey, movement corridors, or nesting perches provided by ever-expanding road and powerline networks, these “subsidized predators” threaten tortoises and other species thanks to subsidies that help support their populations in areas where they might otherwise have been less abundant. Here, we quantified the risk of predation from these subsidized predators on juvenile Mojave desert tortoises by quantifying attack rates on 3D-printed replicas. We evaluated predation risk as a function of replica size, distance from powerlines, and season—variables that can inform release strategies of head-started and translocated tortoises. We found significantly greater risk of predation from ravens in the spring than in the fall. Replica size did not significantly influence predation risk from ravens or coyotes. Replica distance from a powerline or road also did not significantly influence predation risk, supporting previous studies that have found the risk of predation can persist for up to 1.6 km from raven nesting structures. Our results support recommendations for releasing juvenile head-started and translocated tortoises in the fall and away from areas close to raven nesting structures. Our study provides insight into the interactions of prey and subsidized predators and helps guide management on potential mitigation strategies for minimizing the impacts of subsidized predators on species like the imperiled Mojave desert tortoise.